Design and Implementation of Simulation System for Multi-Domain Tactical SDN Using OPNET Modeler - Lee, Seungwoon; Jeong, Yunhwan; Roh, Byeong Hee (Journal of Korean Institute of Communications and Information Sciences, 2020)
Start Software-Defined Networking (SDN) is a future networking architecture that decouples the control plane and the data plane of network devices to provide flexible and economical network management with centralized control. In particular, SDN has the potential in a military tactical network that requires fast and dynamic network management. To evaluate and improve the effectiveness of tactical SDN, Mininet, the most popular SDN tool, was mainly used for simulation, but OPNET Modeler, widely used for tactical network M&S, has released the SDN model and can simulate the more robust environment. However, due to the limitations of the OPNET SDN model, multi-domain simulation is not possible. Because military tactical network consists of heterogeneous systems and requires seamless communication between them, it is necessary to support SDN M&S at the multi-domain environment. In this paper, we design, implement, verify a tactical SDN simulator for multi-domains using multiple OPNETs and additional devices.
Keywords: Military Tactical Network; Modeling and Simulation; Multi-Domain; OPNET; Software Defined Networking